2020
DOI: 10.1101/2020.03.06.973164
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Network structure of the mouse brain connectome with voxel resolution

Abstract: Fine-grained descriptions of brain connectivity are fundamental for understanding how neural information is processed and relayed across spatial scales. Prior investigations of the mouse brain connectome have employed discrete anatomical parcellations, limiting spatial resolution and potentially concealing network attributes critical to the organization of the mammalian connectome.Here we provide a voxel-level description of the network and hierarchical structure of the directed mouse connectome, unconstrained… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
86
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(98 citation statements)
references
References 70 publications
(114 reference statements)
12
86
0
Order By: Relevance
“…This interpretation is supported by empirical and computational evidence suggesting that structural and rsfMRI-based connectivity are robustly related. For example, structural and functional connection strengths are correlated both at the whole-brain and mesoscopic scale (Hagmann et al, 2008;Wang et al, 2013;Coletta et al, 2020), and rsfMRI network topography closely recapitulates patterns of anatomical connectivity (Honey et al, 2009;Goni et al, 2014). In keeping with this, experimental resection of callosal connections (O'Reilly et al, 2013) and chemogenetic inactivation of the amygdala have been shown to reduce functional connectivity with regions anatomically linked to the manipulated areas (Grayson et al, 2016).…”
Section: Introductionmentioning
confidence: 68%
See 4 more Smart Citations
“…This interpretation is supported by empirical and computational evidence suggesting that structural and rsfMRI-based connectivity are robustly related. For example, structural and functional connection strengths are correlated both at the whole-brain and mesoscopic scale (Hagmann et al, 2008;Wang et al, 2013;Coletta et al, 2020), and rsfMRI network topography closely recapitulates patterns of anatomical connectivity (Honey et al, 2009;Goni et al, 2014). In keeping with this, experimental resection of callosal connections (O'Reilly et al, 2013) and chemogenetic inactivation of the amygdala have been shown to reduce functional connectivity with regions anatomically linked to the manipulated areas (Grayson et al, 2016).…”
Section: Introductionmentioning
confidence: 68%
“…Importantly, all the thalamo-cortical regions showing increased rsfMRI connectivity in Kir2.1 mice are characterized by high projections density from the PFC, as seen by comparing the magnitude of intergroup rsfMRI connectivity differences with incoming axonal connectivity strength inferred from a voxel-model of the mouse brain connectome (Coletta et al, 2020) (Fig. 1F, Wilcoxon rank sum test, p<0.0001).…”
Section: Fig S2)mentioning
confidence: 92%
See 3 more Smart Citations